Study of Low Energy Properties of Hadrons Using Phenomenological Models and Effective Theories - Batra, Meenakshi (My University, 2015)
The work presented here is concerned about the theoretical study of static properties of different hadronic systems using statistical models and effective theories. The various aspects of spin 1/2 baryonic systems and heavy-light mesons are analyzed deeply. This thesis is dedicated to the some of the basic questions which are yet unanswered. For example, proton spin crisis and presence of strange quark content inside the nucleonic system. Therefore, the strange quark contributions are explicitly added in the present work by modifying the principle of detailed balance. Statistical model is used to find the answers of some of the queries by using the statistical techniques. The hyperons are also checked against the impact of SU(3) breaking on the different properties of baryons. In addition to this, the latest resonances in the heavy-light mesonic sector are analyzed and few basic properties like masses, splittings and decay widths of some of the charm and bottom mesons are calculated using heavy hadron chiral perturbation theory. The present work also discusses about the possible spin-parity assignments of recently observed states by LHCb collaboration.
PHD, SPMS
Keywords: HQET; Phenomenological Models; Heavy Quarks; Baryon Octet; SU(3) symmetry